Rancang Bangun Mesin Cuci Tangan Otomatis - Melkysedekh S.P.; Janur Ramadan; Gafarudin La Hidi; Raden Rinova Sisworo; Aminur (Program Pendidikan Vokasi Teknik Mesin, 2022)
Hand washing is a simple activity, but it has enormous effects and benefits for health. Especially in this time of the covid-19 pandemic, we all have to wash our hands. Hand washing tools, both manual and automatic, have their respective roles. For manual hand washing tools, we still use our hands to turn the water faucet. So in the process of making this hand washing tool, we aims to design a hand washing machine with an automatic system and implement the design in the form of a product. From the results of the design of the automatic hand washing tool that we made, namely using a 4x4 hollow iron with a tool height of 145 cm and a width of 55 cm, while this automatic hand washing control system we use 4 components consisting of a proximity sensor, relay, IC 7805, electric water pump and produce a hand washing tool that can help make washing hands easier without having to turn the water faucet, because this tool has used a proximity sensor / motion sensor. Then the results of this design still need to be done further research and development, for example, such as adding a hand dryer in order to optimize performance.